GNSS TEXNOLOGIYALARIDAN FOYDALANISHDA ANIQLIK MUAMMOLARI VA ULARNI BARTARAF ETISH YO‘LLARI (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article provides a scientific analysis of accuracy issues encountered in the use of Global Navigation Satellite Systems (GNSS). The effects of the ionosphere and troposphere, multipath signal propagation, satellite geometry, and receiver hardware errors are considered as the main influencing factors. In addition, the role of differential correction methods, RTK technology, and modern data processing algorithms in improving positioning accuracy is discussed. The research findings contribute to the development of practical recommendations for the effective application of GNSS technologies in geodetic and engineering activities.